2011
DOI: 10.1186/1471-2164-12-259
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the venom gland transcriptomes of Costa Rican snakes by 454 pyrosequencing

Abstract: BackgroundA long term research goal of venomics, of applied importance for improving current antivenom therapy, but also for drug discovery, is to understand the pharmacological potential of venoms. Individually or combined, proteomic and transcriptomic studies have demonstrated their feasibility to explore in depth the molecular diversity of venoms. In the absence of genome sequence, transcriptomes represent also valuable searchable databases for proteomic projects.ResultsThe venom gland transcriptomes of 8 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 115 publications
(127 reference statements)
4
79
0
Order By: Relevance
“…To date, most venom transcriptomic studies have used expression data to discover novel toxins, and for this purpose, next-gen sequencing will likely replace the use of cDNA libraries in the near future (Durban et al, 2011;Hu et al, 2011;Whittington et al, 2009). The two next-gen instruments that dominate the current market are the Illumina HiSeq 2000 and the Roche 454 GS FLX+ System.…”
Section: Future Directions In Understanding Venom Adaptationmentioning
confidence: 98%
“…To date, most venom transcriptomic studies have used expression data to discover novel toxins, and for this purpose, next-gen sequencing will likely replace the use of cDNA libraries in the near future (Durban et al, 2011;Hu et al, 2011;Whittington et al, 2009). The two next-gen instruments that dominate the current market are the Illumina HiSeq 2000 and the Roche 454 GS FLX+ System.…”
Section: Future Directions In Understanding Venom Adaptationmentioning
confidence: 98%
“…Because snake venom disintegrins are often derived from proteolytic processing of P-II metalloproteinases, a custom BLAST database of C. s. tzabcan P-II SVMPs was constructed from published data [36]. The sequences obtained for disintegrins in this study were then queried against this database, and exact matches were considered P-II derived disintegrins.…”
Section: Cloning and Sequencing Of Disintegrinsmentioning
confidence: 99%
“…some studies have detected concordance between the abundance of both toxin gene transcripts and proteins in snake venom systems (22,23), many others have demonstrated that the toxin genes detected in venom glands do not correlate well with the composition of secreted venom (7,24), suggesting that some level of regulatory control acts on protein translation. However, most studies typically focused on comparisons at the toxin family level by using a single species, which could be misleading if mechanisms affecting translation act differentially on toxin paralogs and, therefore, result in different outcomes in different species.…”
Section: Significancementioning
confidence: 99%
“…However, the efficacy of these therapies is largely restricted to the snake species whose venom was used in manufacture. This limitation arises because variation in venom composition is ubiquitous at every level of snake taxonomy, including interspecifically and intraspecifically and even ontogenetically (6)(7)(8)(9). Importantly, the extent of this variation is not simply reflected by taxonomic distance (9)(10)(11) and, therefore, cannot be readily predicted.…”
mentioning
confidence: 99%